Geriatric nutritional risk index and controller nutritional status score before metastatic first-line chemotherapy predict survival in patients over 70 years of age with metastatic bladder cancer - Balçık, Onur Yazdan; Demir, Bilgin; Ilhan, Yusuf; Akagündüz, Baran (Frontiers in Medicine, 2024)
Introduction Several prognostic factors have been identified in patients with metastatic bladder cancer (BC). As it is known, older adult patients are prone to nutritional deficiency. The knowledge about nutrition and impact on survival in older patients with metastatic bladder cancer is missing. It is necessary to specifically examine this population. Because timely interventions can make a positive impact on this patients population. This retrospective study aimed to evaluate the prognostic effect of the Geriatric Nutritional Risk Index (GNRI), Controller Nutritional Status (CONUT) score and Prognostic Nutritional Index (PNI) before first-line chemotherapy in the metastatic stage in patients with metastatic bladder cancer over 70. Participants and methods Patients over 70 with pathologically confirmed denovo metastatic or recurrent metastatic bladder cancer were included in the study. Patients with infections diagnosed at the time of diagnosis, autoimmune diseases or history of steroid use were excluded. Since our population consists of a specific age group with a specific cancer, we found a new cut-off value by performing ROC analysis to ensure optimal sensitivity and specificity in terms of progression. Low GNRI value was related with poor nutritional status. Low PNI value was related with poor nutritional status and high CONUT score was related with poor nutritional status. Factors predicting overall survival (OS) and Progression-Free Survival (PFS) were assessed using both univariate and multivariate Cox proportional hazards analyses. Results 106 patients were included in the study and the average age was 75.5 years. In the GNRI-Low group, PFS was significantly shorter than that in the GNRI-High group [HR (95% CI) = 57.1 (12.8–255.5), (p < 0.001)]. Among those with a low-CONUT score, PFS was found to be longer than that in the high-CONUT group [HR (95% CI) = 1.7 (1.0–3.0), (p = 0.039)]. The median PFS of the PNI-Low group wasn’t significantly shorter than that of the PNI-High group [HR (95% CI) = 1.8 (0.5–6.2), (p = 0.359)]. Conclusion Our study suggests that the GNRI and CONUT scores are useful for predicting survival in patients over 70 years of age with BC.